7(n+8)=2-5(n-6)

Simple and best practice solution for 7(n+8)=2-5(n-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(n+8)=2-5(n-6) equation:


Simplifying
7(n + 8) = 2 + -5(n + -6)

Reorder the terms:
7(8 + n) = 2 + -5(n + -6)
(8 * 7 + n * 7) = 2 + -5(n + -6)
(56 + 7n) = 2 + -5(n + -6)

Reorder the terms:
56 + 7n = 2 + -5(-6 + n)
56 + 7n = 2 + (-6 * -5 + n * -5)
56 + 7n = 2 + (30 + -5n)

Combine like terms: 2 + 30 = 32
56 + 7n = 32 + -5n

Solving
56 + 7n = 32 + -5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '5n' to each side of the equation.
56 + 7n + 5n = 32 + -5n + 5n

Combine like terms: 7n + 5n = 12n
56 + 12n = 32 + -5n + 5n

Combine like terms: -5n + 5n = 0
56 + 12n = 32 + 0
56 + 12n = 32

Add '-56' to each side of the equation.
56 + -56 + 12n = 32 + -56

Combine like terms: 56 + -56 = 0
0 + 12n = 32 + -56
12n = 32 + -56

Combine like terms: 32 + -56 = -24
12n = -24

Divide each side by '12'.
n = -2

Simplifying
n = -2

See similar equations:

| 8x+1y=26 | | =3x^2-9x | | -15+31=-2(x+1) | | 2(5h)+25=40h | | -16z-0.7=-26z+2.1 | | 81a^2=4 | | 0=x^2-9x^4 | | 2ln(y)=y | | 5(3+8)=(X*3)+(X*8) | | 8r+9r=-21 | | (2x-8)-10=2-8x | | 9x+40=x-16 | | 5h(p)+25=20h(p) | | 3(n+7)=7-4(n-7) | | 8xsquared-47x-6=0 | | 2+8=33(2x) | | 5h+25=20h | | X^2-8x+6=f(x) | | 7(4m-3)= | | f(x)=x^2-9x^4 | | 127=4(2*c) | | 264/26 | | 127=4+2c | | 12m+4m-3m= | | x-25.4=59.6 | | 3+7=5+v | | 3/8y-1/6=1/5 | | 375/800 | | 4n=n-21 | | 48a^3k2/6a^2k | | 775/800 | | 5p-2(-p-1)-7=p-(-8-p)-12 |

Equations solver categories